Improvement on the quality of chilli (Capsicum annuum L.) seedlings through seed immersion in Supergib solution. Issue 4 (July 2021) - Syaiful, Syatrianty A.; Haring, F; Syawlia, R R; Padjung, R; Mantja, K; Farid, M
Abstract: This study aims to obtain the best supergib concentration and immersion ime that affect the growth of chili plant seeds. The study consisted of two stages, namely viability and vigor test of seeds which was carried out at the Laboratory of Plant Breeding and Seed Science, Department of Agronomy, Faculty of Agriculture, Hasanuddin University. The second stage is the chili plant nursery which is held at the Faculty of Agriculture, Hasanuddin University, Makassar. The study was conducted from December 2019 to February 2020. This study used a two-factor factorial randomized block design, with the concentration of supergib as the first factor consisted of 4 levels, namely 0 ppm, 10 ppm, 15 ppm and 20 ppm. The second factor was the length of soaking time which consisted of 3 levels, namely 6 hours, 9 hours, and 12 hours. The results show that the 10 ppm supergib concentration and 12 hours of soaking the seeds gave the best results at the growth rate of 19.35% and the supergib concentration of 15 ppm and the duration of soaking for 9 hours gave the best results on the primary root length of the sprouts (3.68 cm), plant height (11.77 cm) and the number of leaves (6.67). Soaking time for 6 hours resulted in the highest average germination capacity of 65%, and treatment for 9 hours of immersion resulted in the highest growth simultaneous value of 25.67%.